Surface count of follicles during different phases of reproductive cycle in the ovaries of Indian buffaloes - Bansal, Neelam; Saigau, R P (The Indian Journal of Animal Sciences, 2011)
The study was conducted to evaluate the biometry of different types of follicles visible on the surface of buffalo ovary;their count and classification on the basis of their size and thereby to assess the ovarian fo Hiele growth and activity in relation to reproductive cycle in buffaloes. The ovaries were collected in pairs from 53 adult buffaloes (3.515 years ofage) and divided into follicular, early-luteal, mid-luteal and late-luteal phases of reproductive cycle on the basis of ovarian condition. The ovarian follicles were measured and classified into 3 categories Le. small (1-4 mm), medium (>4-8 mm) and large (>8 mm) follicles. The number ofsmall size follicles was higher as compared to medium and large size follicles. There was no significant difference observed between average number of follicles per ovary visible on the surface of left and right sides, the values being 9.13 for left and 8.68 for right ovaries. The classification offollicles into different categories showed that the large-size follicles on right ovaries was significantly higher (65.0%) as compared to that (35.0%) on left ovari'es. The average number of small follicles was observed to be significantly (P